Increased Knowledge and Attitudes of Preconception Care using the Dedi Torri Application: Peningkatan Pengetahuan dan Sikap Perawatan Prakonsepsi melalui Aplikasi Dedi Torri - Ni nyoman Y. Abriyani; Tri Sunarsih; Luluk Rosida (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objetive: To determine the increase in knowledge and attitude of preconception care through the application of DeDitorRi.Methods: Uses pre-experiment using a one group pre-test and post-test design.Result: Based on the paired t test in the first health education using the DeDi torRi application to the difference in knowledge obtained with a p value of 0.000 in attitudes with a p value of 0.000. Based on paired t test in the second health education using the DeDitorRi application to the difference of knowledge obtained with a p value of 0.000 and an attitude with a p value of 0.000.Conclusion: Preconception care health education through DeDi torRi (application-based module) and education that is given repeatedly to reproductive age mothers can influence the increase in knowledge and attitude of preconception care.Keywords: health education applications, preconception care, women of reproductive. Abstrak Tujuan : Untuk mengetahui peningkatan pengetahuan dan sikap perawatan prakonsepsi melalui aplikasi DeDi torRi. Metode : Pre-eksperimen dengan menggunakan rancangan one group pre-test dan post-test.Hasil: Berdasarkan uji paired t test pada pendidikan kesehatan pertama menggunakan aplikasi DeDi torRi terhadap beda pengetahuan yang didapatkan dengan p value sebesar 0,000 pada sikap dengan p value 0,000. Berdasarkan uji paired t test pada pendidikan kesehatan kedua menggunakan aplikasi DeDi torRi terhadap beda pengetahuan yang didapatkan dengan p value sebesar 0,000 dan pada sikap dengan p value 0,000.Kesimpulan: Pendidikan kesehatan menggunakan aplikasi DeDi torRi (aplikasi berbasis modul) efektif dalam meningkatkan pengetahuan dan sikap pada perempuan usia reproduktif terhadap perawatan prakonsepsi. Kata kunci: aplikasi pendidikan kesehatan, perawatan prakonsepsi, perempuan usia reproduktif.